Development of Pharmacy Inventory Management System (PIMS) by implementing ABC analysis for Farmasi Hijrah / Nurfarahin Azahar - Azahar, Nurfarahin (2017)
This project is an attempt to implement the ABC analysis in order to control the inventory costs and suggests that past inventory problems in this pharmacy are largely due to the crowd of inventory and the use of inappropriate computer package that computer package has on inventory. It is also pointing out that due to these problems some parts take too much time to find at the time of need, which affects the working efficiency of the pharmacy. There are also problem with very high annual usage rate. This happened due to the ordering that has been made based on the inventory checking. The methodology that will be uses in this project is waterfall methodology which is consists of 4 phases. The first phases are Requirements Identification phase. The second one is Analysis phase. The third one is Design phase and last but not least is Development and Implementation phase. Therefore, in order to solve the problem of inventory cost this project will be implementing ABC Analysis in the development of Pharmacy Inventory Management System (PIMS) for Farmasi Hijrah.In future work, it is proposed other developers would be improving this system in term of ordering and sales.